Development of a moodle-based "siparti" (participatory synergy) academic supervision model to enhance elementary school teachers' pedagogical competence - Maria Magdalena Deti Irmawanti; Listyani Listyani; Sophia Tri Satyawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to develop a Moodle-based Academic Supervision Model, "SiParti" (Participatory Synergy), to enhance elementary school teachers' pedagogical competence. The research employed a Research and Development (R&D) approach adapted from Sugiyono's model, with the stages limited to the first product revision phase. The research subjects consisted of five teachers (ranging from junior to senior levels), one principal, one school committee member, and two expert validators (a supervision expert and an ICT expert). The research instruments included validation sheets, feasibility questionnaires, and user satisfaction surveys. The results of the material expert validation indicated a feasibility percentage of 88.3%, categorized as "Highly Feasible," while the ICT expert validation obtained 80%, categorized as "Feasible." Field testing demonstrated a user satisfaction rate of 95.1%, categorized as "Very High," particularly in aspects of collaboration, system security, and ease of use. The SiParti model integrates the stages of Si (Preparation), Par (Observation), and Ti (Follow-up) digitally through a role-based access control (RBAC) system to ensure data security and teacher professionalism. These findings indicate that the Moodle-based SiParti Academic Supervision Model is valid, feasible, and effective as a digital collaborative supervision innovation in supporting the sustainable improvement of elementary school teachers' pedagogical competence.